2021
DOI: 10.1177/00027642211051616
|View full text |Cite
|
Sign up to set email alerts
|

The Multifaceted Impact of COVID-19: Health, Emotions, Well-Being, and Risk Assessment

Abstract: Analyzing diverse and rich data on the COVID-19 pandemic, this issue of the American Behavioral Scientist offers important insights into health and risk assessment in a time of unprecedented crisis in the 21st century. This issue explores health, emotions, and well-being vis-à-vis the pandemic and its societal impacts. Across the articles, we see the complex ways that this global health crisis has consequences for individuals and groups as they engage in risk assessment and grapple with the secondary effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The effects of this pandemic, which has caused almost 7 million deaths as of January 2024, 4 are numerous and multifaceted. [5][6][7] The medical picture is primarily respiratory dysfunction, but the clinical impacts include multisystem damage 6,8 and the effects on the cardiovascular system are among the most important secondary impacts of COVID-19. 9,10 Since the early days of the pandemic, studies from many countries around the world have reported a decrease in ACS-related hospital admissions, [11][12][13] potentially explained by lockdowns and fear of spread.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of this pandemic, which has caused almost 7 million deaths as of January 2024, 4 are numerous and multifaceted. [5][6][7] The medical picture is primarily respiratory dysfunction, but the clinical impacts include multisystem damage 6,8 and the effects on the cardiovascular system are among the most important secondary impacts of COVID-19. 9,10 Since the early days of the pandemic, studies from many countries around the world have reported a decrease in ACS-related hospital admissions, [11][12][13] potentially explained by lockdowns and fear of spread.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of this pandemic, which has caused almost 7 million deaths as of January 2024, 4 are numerous and multifaceted. 5 - 7 …”
Section: Introductionmentioning
confidence: 99%